Felicitous Life with an Emphasis on Islamic Teachings - Hatami, Mohammadreza (Universitas Muhammadiyah Surakarta, 2024)
A felicitous life has always been the concern of the Islamic society and the present paper aims to explore the documents of Islamic teachings that refer to this issue. The research seems necessary to determine the basic dimensions of life to become operational. In this regard, the present paper tries to study Islamic teachings related to felicitous life and describe and examine its important dimensions using descriptive and analytical methods. By searching the two concepts of